Caracterização dos elementos generativos em Casearia lasiophylla Eichl. - Schoenberg, Maria Miranda; Schimmelpfeng, Luiz Carlos T. (Acta Biológica Paranaense, 1984)
Caracterização dos elementos generativos em Casearia lasiophylla Eichl.